The Impact of Structured Parenting on Strengthening Interpersonal Collaboration in Addressing Complex Social Phenomena - Fakhruddin, Asef Umar; Ain M.Y, Siti Nurul (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2025)
Abstract:Â Structured parenting is no longer merely an option but an urgent necessity. Interpersonal collaboration facilitated by structured parenting enables individuals understand their identities, aspirations, and appropriate behaviors in an evolving environment, thus helping them navigate complex social dynamics. Employing a quantitative analysis approach as proposed by John Creswell and a qualitative analysis based on Pierre Bourdieuâ€™s habitus theory, this study examines the influence of structured parenting on strengthening interpersonal collaboration in addressing the social complexities. Based on data from 500 respondents and a combination of quantitative and qualitative methodologies, this study finds that: (1) structured parenting significantly enhances social skills (p < 0.05); (2) it contributes to conflict resolution within communities (p < 0.05); (3) it strengthens social collaboration within society (p < 0.05); and (4) the regression model indicates that rule consistency has the most significant impact on reinforcing interpersonal collaboration in addressing complex social dynamics (Î² = 0.42). Furthermore, structured parenting improves educational quality, skill development, and readiness to face an increasingly competitive workforce. By instilling a visionary, creative, hardworking, innovative, and socially responsible mindset, future generations will be better equipped to address escalating social and economic inequalities. These findings serve as a basis for further recommendations. Key Words:Â Complex Social Phenomena, Interpersonal Collaboration, Structured ParentingÂ